Photometrics analysis of frontal and facial profiles of class II division 1 skeletal malocclusion patients before and after compromised orthodontic treatment (proffit and steiner analysis): Study descriptive - mulkhairul, Ilham; Mardiati, Endah; Laviana, Avi; Evangelina, Ida Ayu (Padjadjaran Journal of Dental Researchers and Students, 2024)
ABSTRACTIntroduction: The aesthetics of the face is a concern in orthodontic treatment as it directly relates to appearance.. Class II division 1 malocclusion patients often exhibit a convex facial profile, which frequently affects facial aesthetics. The aim of this study is to determine the differences in frontal photometry using the Proffit method and profile photometry using the Steiner method in Class II division 1 skeletal malocclusion patients before and after compromised orthodontic treatment. Methods:  This was a descriptive analytical comparative study. The sample population was determined through purposive sampling of compromised orthodontic treatment patients with Class II division 1 malocclusion treated at the Orthodontic PPDGS Clinic, RSGM Unpad, from 2016 to 2021, totaling 11 patients. Paired t-test were used to analyze the differences in frontal photometry using the Proffit method and profile photometry using the Steiner method in Class II division 1 skeletal malocclusion patients before and after compromised orthodontic treatment. (p – value < 0.05). Results: There were significant differences in the lower third of facial height (p-value 0.0023 < 0.05) and the position of the upper lip relative to the S-line (p-value 0.0014 < 0.05). There were no significant differences in the upper third of facial height, facial proportions from helixsrt – exochantion (exrt), facial proportions from exochantion (exrt) – endochantion (enrt), facial proportions from endochantion (enrt) - endochantion (enlt), proportions face from endochantion (enlt) – exochantion (exlt), facial proportions from exochantion (exlt) – helixslt, position of the lower lip relative to the S-line (p-value > 0.05). Conclusion: Compromised orthodontic treatment for Class II division 1 malocclusion with extraction of two upper premolars results in change to soft tissue profile in the lower third of facial height and the position of the lower lip relative to the S-line, as analyzed by frontal photometry using the Proffit method and profile photometry using the Steiner method.KEY WORDS: skeletal malocclusion class II division 1, compromised treatment, Proffit, and Steiner analysisAnalisis fotometri frontal dan profil wajah pasien maloklusi skeletal kelas II Divisi 1 sebelum dan setelah perawatan ortodonti kompromi (Metode Proffit dan Steiner): Studi deskriptifABSTRAKPendahuluan: Estetika wajah menjadi perhatian dalam perawatan ortodonti karena berhubungan langsung dengan penampilan. Pasien maloklusi kelas II divisi 1 mempunyai wajah cembung dan sering kali mengganggu estetik wajah. Tujuan penelitian mengetahui perbedaan fotometri frontal metode Proffit dan fotometri profil metode Steiner pasien maloklusi skeletal kelas II divisi 1 sebelum dan setelah perawatan ortodonti kompromi. Metode: Penelitian bersifat deskriptif analitis komparatif. Populasi sampel ditentukan secara purposive sampling terhadap pasien perawatan ortodonti kompromi maloklusi kelas II divisi 1 yang dirawat di klinik PPDGS Ortodonti RSGM Unpad tahun 2016-2021, sejumlah 11 pasien. Uji t-test berpasangan digunakan untuk menganalisis perbedaan fotometri frontal metode Proffit dan fotometri profil metode Steiner pasien maloklusi skeletal kelas II divisi 1 sebelum dan setelah perawatan ortodonti kompromi. (p – value < 0,05). Hasil: Terdapat perbedaan yang signifikan pada tinggi wajah sepertiga bagian bawah (p-value 0,0023 < 0,05) dan posisi bibir atas terhadap S-line (p-value 0,0014 < 0,05). Tidak terdapat perbedaan yang signifikan pada tinggi wajah sepertiga bagian atas, proporsi wajah dari helixsrt – exochantion (exrt), proporsi wajah dari exochantion (exrt) – endochantion (enrt), proporsi wajah dari endochantion (enrt) – endochantion (enlt), proporsi wajah dari endochantion (enlt) – exochantion (exlt), proporsi wajah dari exochantion (exlt) – helixslt, posisi bibir bawah terhadap S-line (p-value > 0,05). Simpulan: Perawatan ortodonti kompromi maloklusi kelas II divisi I dengan pencabutan dua premolar rahang atas menghasilkan perubahan profil jaringan lunak pada sepertiga wajah bagian bawah dan posisi bibir bawah terhadap S-line, berdasarkan analisis fotometri frontal metode Proffit dan fotometri profil metode Steiner.KATA KUNCI: maloklusi skeletal kelas II divisi 1, perawatan kompromi, analisis Proffit, dan Steiner.